Pengembangan Potensi Daerah (Madu) Sebagai Desa Wisata Edukasi Coduzinc (Cookies Madu Zinc) - Nurul Amelinda Dwi Fatimah; Mar'atus Sholichah, Rizka (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
Kampung Madu is the Purworejo Hamlet nickname, located in Bringin Village, Badas District, Kediri Regency, East Java Province. The aim of the P2MD program for the Karya Husada Kediri Nutrition Academy Student Senate is to develop the potential of Kampung Madu by creating coduzinc educational tours and creating innovations in honey zinc cookies and being able to develop the potential of Kampung Madu. The methods used in this activity are location surveys, conducting outreach related to plans to develop the potential of the coduzinc educational tourism village, holding training on making coduzinc (honey zinc cookies), holding educational training on rice planting, holding educational training on bee farming, launching an educational tourism village, holding a coloring competition event, holding counseling on PHBS and hand washing, and conducting a test of acceptability of "zinc honey cookies" coduzinc, the results of P2MD activities are creating a honey village as an educational tourism village, producing an innovation based on commodities, increasing knowledge and skills about washing the hands of Dharma Wanita Kindergarten children properly and correctly, and conducting evaluations the acceptability of "CODUZINC" Zinc Honey Cookies among Dharma Wanita Kindergarten Students and conducted a test of the acceptability of coduzinc "zinc honey cookies." At the launching event on October 28, 2023, 102 people attended. On November 18, a coloring competition was held at the Coduzinc educational tourism site which 107 people attended. Based on the launching and competition activities, there was an increase in visitors to the Coduzinc educational tourism village by 5%. At the Dharma Wanita Village Kindergarten. Bringin (85%) children can wash their hands according to the correct steps, Kindergarten students' acceptance of CODUZINC products with a 0% food waste score scale is 50% of toddlers, Kindergarten students' acceptance of CODUZINC products in the good category is 55%.